Advanced turbulence modelling for complex aerospace applications. - Enda Dimitri Vieira Bigarella (2007)
The objective of the present research work consists in studying complex aerodynamic flows about typical aerospace configuration, in which turbulence effects play a fundamental role. Such study is performed with an available computational tool that is being developed at CTA/IAE. This is a finite-volume code for unstructured 3-D meshes that solves the compressible Reynolds-averaged Navier-Stokes equations. Turbulence effects are added to this numerical tool through turbulence models. Similar work had already been initiated by the author in his master thesis at ITA with less advanced model in that context. Turbulence effects are critical for complex aerospace configurations, such as supercritical or high-lift aerofoils, or space vehicles at atmospheric transonic or supersonic flight, and less advanced turbulence models fail to adequately describe such flows. The investment in more complex turbulence models, such as {em nonlinear} eddy viscosity and Reynolds-stress transport closures, is of fundamental importance to better capture such flows, which are very important in the context of the developments within the aerospace area at CTA/IAE and Embraer. Furthermore, in order to allow for a robust and efficient numerical framework, effort is also driven towards convergence acceleration techniques such as multigrid and variable time stepping procedures, as well as convective flux computation schemes suitable for boundary layer and shocked flows. These flux schemes must be robust and accurate even for highly stretched meshes that support these flow phenomena at reasonable computational costs. The validation of these new implementations, for the applications of interest, is performed by comparison of numerical results with experimental or theoretical data for several flow cases. Flows involving laminar boundary layers and shock waves are used to assess the quality of the convective flux computation schemes. Traditional turbulent-flow validation cases, such as the turbulent boundary layers over a flat plate or within a parallel-wall channel, are considered to address the level of physical representativeness of the chosen models. Finally, typical aerospace flows are evaluated with the best numerical settings resulting from the previously mentioned efforts. Such cases involve transonic and high-lift aerofoils, and transonic and supersonic flows about a space vehicle. In general, good agreement of numerical results with the reference data is obtained.